Formulation and evaluation of sundried tomatoes on nutritional, sensory acceptability and storage - P. LAKSHMI REDDY, K. SUDHA RANI, A. MALLISWARA REDDY, A.B. SRINATH REDDY, AND (The Journal of Research, PJTSAU, 2017)
A study was conducted at Krishi Vigyan Kendra, Reddipalli, Anantapur, on the sundried tomato products (pieces/powder) and the objective of the study is to maintain the fluctuation in prices during glut season and to reach the consumer during high price period. In the present study tomato powder was assessed for its storage stability, nutritive analysis of lycopene, ascorbic acid and total bacterial and microbial count, simultaneously the samples were analysed at each 30 days interval for sensory attributes(colour, taste, consistency (texture), appearance, and overall acceptability). The results revealed that the storage of tomato powder for 3 months without negligible loss of lycopene & vitamin C and total bacterial and microbial counts were below detectable levels. The acceptance level of the powder was equivalent to the fresh tomatoes by the panel members.